Detection of hydrocarbons in clay soils: A laboratory experiment using spectroscopy in the mid- and thermal infrared - Meijde, M., van der; Knox, N; Cundill, S.L; Noomen, M.F; Werff, H.M.A., van der; Hecker, C (ITC journal, 2013)
Remote sensing has been used for direct and indirect detection of hydrocarbons. Most studies so far focused on indirect detection in vegetated areas. We investigated in this research the possibility of detecting hydrocarbons in bare soil through spectral analysis of laboratory samples in the short wave and thermal infrared regions. Soil/oil mixtures were spectrally measured in the laboratory. Analysis of spectra showed development of hydrocarbon absorption features as soils became progressively more contaminated. The future application of these results airborne seems to be a challenge as present and future sensors only cover the diagnostic regions to a limited extent